Experimental investigation of the characteristics of a jet-ejector and a jet-ejector cooling system operating with R134a as a refrigerant. (August 2015) - Zegenhagen, M.T.; Ziegler, F.
Abstract: Due to their simplicity, jet-ejector cooling systems have been investigated for different applications despite their lower thermal COP th in comparison to alternative thermally-driven cooling technologies. The present paper aims at the derivation of a simple method of representation of the operation characteristics of a jet-ejector cooling system for changing boundary conditions. Thereto, a jet-ejector cooling system operating with the refrigerant R134a has been experimentally investigated in double choking operation of the jet-ejector. The jet-ejector operation is characterized by the entrainment ratio μ in dependence of the adequate stagnation pressure ratios. The results are discussed in a non-dimensional graph as a three dimensional surface from which characteristic lines may be deduced. In several graphs, the motive, condenser and evaporator pressures are linked with the entrainment ratio μ, the cooling capacity Q ˙ 0, the thermal COP th and the hydraulic COP h allowing a comprehensive determination of the system operation. Highlights: Experimental deduction of a plane of the jet-ejector double choking operation. Derivation of characteristic curves of the critical jet-ejector operation. Investigation of the influence of the motive superheating on operation. Analysis of thermal COP, hydraulic COP and cooling capacity of the system. Introduction of a nomogram for critical jet-ejector system operation.